Comparison of the healing property of sugar gels and Passiflora edulis (Research, Society and Development, 2022)
The treatment of surgical and non-surgical wounds has become an increasing challenge in veterinary medicine, due to resistance to antimicrobial drugs and the fact that these animals end up ingesting topical drugs, often causing side effects and intoxication of these. animals, generating greater difficulties in the treatment and healing process of continuity solutions. In this way, searching for the formulation of new topical drugs that have the ability to treat wounds, accelerate healing and that can also be ingested by the patient, if the species has the habit of licking itself, is extremely important in veterinary medicine. With the aim of developing of a drug with these characteristics, this project formulated three gels, with natural ingredients - crystal sugar and Passiflora edulis (passion fruit) pulp, which can be ingested by animals, and that after literary research, it was possible to verify that these products have active principles that help in the healing of these wounds, fact corroborated at the end of the research. This research was approved by the CEUA (committee of ethics for animal use) of UniSALESIANO de Araçatuba – SP, with protocol nº121.